Heparin-induced tau filaments are structurally heterogeneous and differ from Alzheimer's disease filaments. Issue 36 (17th April 2018) - Fichou, Yann; Vigers, Michael; Goring, Andrew K.; Eschmann, Neil A.; Han, Songi
Abstract : Tau filaments formed with heparin are structurally different from Alzheimer's disease filaments extracted from human brains. Heparin creates heterogeneous filaments in which tau proteins are locally stretched and have minimal large-domain structuration. Abstract : Alzheimer's disease (AD) is characterized by the presence of tau filaments in the brain whose structure was recently solved. The formation of AD filaments is routinely modeled in vitro by mixing tau with heparin. This study shows that heparin-induced tau filaments are markedly different from the AD filaments and are highly heterogeneous.